Budidaya Jamur Tiram Putih (Pleurotus ostreatus) di Desa Payakabung, Kecamatan Indralaya Utara, Kabupaten Ogan Ilir, Provinsi Sumatera Selatan - Rahayu, Rafael Ika; Pratama, Rahmat; Umayah, Abu; Saputra, M. Ramadhan; Jo Andreansya, Destian; Billah, Ela Aisyah; Saputri, Kharisma Ayu; Ningsi, Selvi Yulia (Seminar Nasional Lahan Suboptimal, 2024)
Rahayu, R. I., Pratama, R., Umayah, A., Saputra, M. R., Andreansya, D, J., Billah, E, A., Saputri, K., A. & Ningsi, S. Y. (2024). Cultivation of white oyster mushroom (Pleurotus ostreatus) in Payakabung Village, North Indralaya District, Ogan Ilir Regency, South Sumatera Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 720–730).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).White Oyster Mushroom (Pleurotus ostreatus) is a unique mushroom with a high market price, although the cultivation of white oyster mushrooms has become one of the agricultural product development efforts in Indonesia. The purpose of this research was to find out what ingredients are really and how they affect the cultivation of white oyster mushrooms, as well as their development in the blog. White oyster mushrooms have a very high value in food production and cultivation. The use of baglogs is one of our studies in the development of white mushrooms. One important factor in harvesting high quality mushrooms is the durability and quality of the mushrooms themselves. The more optimal the harvesting method, the better the durability and quality of the picked mushrooms. Conclusions are based on the results obtained, taking into account the formulation of the problem and the objectives of the study. The stages of Mr. Eko Supandi's white oyster mushroom cultivation process are making a barn, preparing and making seedlings, making planting media or baglogs which consist of several stages, namely preparation of planting media, mixing ingredients and composting, packaging media, pasteurization, the next stage of seedling inoculation, incubation of seedlings for 40-60 days, baglog maintenance, harvesting and post-harvest.